Synthesis, anti-aging and mechanism of magnolol derivatives - Pang, Xinxin; Mao, Li; Ye, Danyang; Wang, Wenqi; Yang, Hongliu; Fan, Xiaoxiao; Yang, Yuping; Su, Zhijun; Ma, Tao; Sun, Mingqian; Liu, Yonggang (Frontiers in Chemistry, 2023)
Magnolol (M), a hydroquinone containing an allyl side chain, is one of the major active components of Houpoea officinalis for antioxidation and anti-aging. To enhance the antioxidant activity of magnolol, the different sites of magnolol were structurally modified in this experiment, and a total of 12 magnolol derivatives were obtained. Based on the preliminary exploration of the anti-aging effect of magnolol derivatives in a Caenorhabditis elegans (C. elegans) model. Our results indicate that the active groups of magnolol exerting anti-aging effects were allyl groups and hydroxyl on the phenyl. Meanwhile, the anti-aging effect of the novel magnolol derivative M27 was found to be significantly superior to that of magnolol. To investigate the effect of M27 on senescence and the potential mechanism of action, we investigated the effect of M27 on senescence in C. elegans. In this study, we investigated the effect of M27 on C. elegans physiology by examining body length, body curvature and pharyngeal pumping frequency. The effect of M27 on stress resistance in C. elegans was explored by acute stress experiments. The mechanism of M27 anti-aging was investigated by measuring ROS content, DAF-16 nuclear translocation, sod-3 expression, and lifespan of transgenic nematodes. Our results indicate that M27 prolonged the lifespan of C. elegans. Meanwhile, M27 improved the healthy lifespan of C. elegans by improving pharyngeal pumping ability and reducing lipofuscin accumulation in C. elegans. M27 increased resistance to high temperature and oxidative stress in C. elegans by reducing ROS. M27 induced DAF-16 translocation from cytoplasm to nucleus in transgenic TJ356 nematodes and upregulated the expression of sod-3 (a gene downstream of DAF-16) in CF1553 nematodes. Furthermore, M27 did not extend the lifespan of daf-16, age-1, daf-2, and hsp-16.2 mutants. This work suggests that M27 may ameliorate aging and extend lifespan in C. elegans through the IIS pathway.